1982 - Fujiwara, Simon, 1982-; Amado, Miguel, 1973-; Exhibition. Tate St Ives. 2012-01, 18 (London : Tate publishing, 2012)
Simon Fujiwara (b. 1982) has exhibited internationally, including at the Venice Biennale, and received the Cartier Award 2010. Through novels, theatre plays, lectures and installations, Fujiwara scripts and performs his own biography as fiction - a drama in which he plays the roles of multiple characters: artist, novelist, anthropologist, eroticist, architect and playwright. Fujiwara fuses the personal with grand socio-political and historical themes. Accompanying a major exhibition at Tate St Ives, this is closer to an artist's book in appearance than a conventional exhibition catalogue, yet it will be the most thorough exploration of the work of this important emerging artist yet published.--Tate website.
Includes supplement.
Exhibition 18 January-7 May 2012
boek
Keywords: Fujiwara, Simon